2015
DOI: 10.1063/1.4917228
|View full text |Cite
|
Sign up to set email alerts
|

Electric-field-driven magnetization reversal in square-shaped nanomagnet-based multiferroic heterostructure

Abstract: Articles you may be interested inSimultaneous imaging of the ferromagnetic and ferroelectric structure in multiferroic heterostructures APL Mat. 2, 076109 (2014); 10.1063/1.4890055Giant magneto-impedance effect in amorphous ferromagnetic wire with a weak helical anisotropy: Theory and experiment Based on phase field modeling and thermodynamic analysis, purely electric-field-driven magnetization reversal was shown to be possible in a multiferroic heterostructure of a square-shaped amorphous Co 40 Fe 40 B 20 nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…136,137 However, these proposals rely on the use of either a rotating piezostrain, 136 or a single-crystal magnet that shows two mutually perpendicular magnetic easy axes due to a four-fold magnetocrystalline anisotropy. 137 Recently, it has been shown that two pre-existing and mutually perpendicular magnetic easy axes can also appear in a flower-shaped magnetic nanodot with a fourfold shape anisotropy, 138 or in a square-shaped magnetic nanodot 139 with a four-fold magnetic configurational anisotropy 140 (see schematic in Fig. 7b).…”
Section: Searching For New Magnetoelectric Coupling In Superlatticesmentioning
confidence: 99%
See 2 more Smart Citations
“…136,137 However, these proposals rely on the use of either a rotating piezostrain, 136 or a single-crystal magnet that shows two mutually perpendicular magnetic easy axes due to a four-fold magnetocrystalline anisotropy. 137 Recently, it has been shown that two pre-existing and mutually perpendicular magnetic easy axes can also appear in a flower-shaped magnetic nanodot with a fourfold shape anisotropy, 138 or in a square-shaped magnetic nanodot 139 with a four-fold magnetic configurational anisotropy 140 (see schematic in Fig. 7b).…”
Section: Searching For New Magnetoelectric Coupling In Superlatticesmentioning
confidence: 99%
“…7b). Using micromagnetic phasefield simulations, it was further shown that applying a bipolar 138 or unipolar 139 piezostrain pulse along the y-axis can switch the magnetization by 180°through two consecutive clockwise 90°m agnetization switching (see the arrows in Fig. 7b).…”
Section: Searching For New Magnetoelectric Coupling In Superlatticesmentioning
confidence: 99%
See 1 more Smart Citation
“…Strains/stresses couple to the magnetization via so-called magnetostrictive effect and modify the magnetic anisotropy. 7,8 As a consequence, strains/stresses have effects on the stability and transformation of polar and vortex states in submicron magnetic systems. Indeed, previous studies have shown that the direction of magnetization in the polar state can be reoriented by strain, which indicates the potential application in magnetic random access memory.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there have been several theoretical schemes to realize electric-field-tuned 180 • magnetization switching. 59,60 In the proposition, a flower-shaped 59 or square-shaped 60 nanomagnet with a fourfold symmetric shape anisotropy was deposited on FE materials. Significantly, there is a small angle mismatch between the anisotropic strain and the easy axis of the shape anisotropy resulting in a small energy barrier so that the magnetization can overcome this barrier with the assistance of an electric field.…”
mentioning
confidence: 99%